Emerging Bioactive Agent Delivery-Based Regenerative Therapies for Lower Genitourinary Tissues - Lin-Cui Da; Yan Sun; Yun-Hong Lin; Su-Zhu Chen; Gang-Xin Chen; Bei-Hong Zheng; Sheng-Rong Du (MDPI AG, 2022)
Injury to lower genitourinary (GU) tissues, which may result in either infertility and/or organ dysfunctions, threatens the overall health of humans. Bioactive agent-based regenerative therapy is a promising therapeutic method. However, strategies for spatiotemporal delivery of bioactive agents with optimal stability, activity, and tunable delivery for effective sustained disease management are still in need and present challenges. In this review, we present the advancements of the pivotal components in delivery systems, including biomedical innovations, system fabrication methods, and loading strategies, which may improve the performance of delivery systems for better regenerative effects. We also review the most recent developments in the application of these technologies, and the potential for delivery-based regenerative therapies to treat lower GU injuries. Recent progress suggests that the use of advanced strategies have not only made it possible to develop better and more diverse functionalities, but also more precise, and smarter bioactive agent delivery systems for regenerative therapy. Their application in lower GU injury treatment has achieved certain effects in both patients with lower genitourinary injuries and/or in model animals. The continuous evolution of biomaterials and therapeutic agents, advances in three-dimensional printing, as well as emerging techniques all show a promising future for the treatment of lower GU-related disorders and dysfunctions.